The influence of parents’ socio-economic status and learning motivation of Junior high School learners’ on their future education orientation - Titik Yuliati (Nalar Global Foundation, 2021)
The purpose of this study was to determine the influence of parents' socio-economic status and learning motivation on the future orientation of education for junior high school students in Kunto Darussalam District. This study uses quantitative research methods, with the type of correlation research. Collecting data using observation, questionnaires and documentation. The primary data in this research is by distributing questionnaires to the respondents, namely the students of SMP Negeri Kunto Darussalam. The sampling technique used is simple random sampling, which is 10% of the total population of 92 students. The results of the analysis show that the value of R2 (coefficient of determination) or R square is 0.353 or 35.3%. This value gives an understanding that the variables of parents' socioeconomic status and learning motivation can have an influence on the future orientation of education for state junior high school students in Kunto Darussalam sub-district, which is 35.3%. And this is included in the category of sufficient accuracy in influencing. While the remaining 64.7% is influenced by other variables that are not included in this research model.